Mindfulness and progressive muscle relaxation as standardized session‐introduction in individual therapy: A randomized controlled trial. Issue 1 (8th October 2018) - Mander, Johannes; Blanck, Paul; Neubauer, Andreas B.; Kröger, Paula; Flückiger, Christoph; Lutz, Wolfgang; Barnow, Sven; Bents, Hinrich; Heidenreich, Thomas
Abstract: Objective: There is scarce research on the effects of mindfulness in individual therapy. As many practitioners integrate mindfulness exercises into individual therapy, empirical evidence is of high clinical relevance. Method: We investigated the effects of a session‐introducing intervention with mindfulness elements (SIIME) in a randomized, controlled design. The effects of SIIME on therapeutic alliance and symptomatic outcome were compared with progressive muscle relaxation (PMR) and treatment‐as‐usual (TAU) control conditions. The sample comprised 162 patients with anxiety and depression. Results: Multilevel modeling revealed a significant symptom reduction and significant increase of alliance over the course of therapy. There were no significant time–condition interactions on outcome and alliance, indicating the comparable efficiency of all three treatment conditions. Conclusions: We found no advantage of SIIME versus PMR and TAU. Add‐on mindfulness might not improve individual therapy related to alliance and outcome.